Establishing Cluster System To Higher Education In Teaching English (Open Academia: Journal of Scholarly Research, 2023)
The study aims at discovering the present scenario and the reasons for these challenges. This paper also prescribes to the learners some ways for developing writing skills so that they can apply them in their academic life. Data was collected using a questionnaire which was formulated on the basis of different processes of writing and classroom practice by the learners. The survey was conducted among the students who were studying or had taken language skills courses at the Department of English in a private university of Uzbekistan. Based on the findings, some practical recommendations have been made for all three stakeholders: learners, teachers, and institutions.